2019
DOI: 10.2147/trrm.s183382
|View full text |Cite
|
Sign up to set email alerts
|

<p>Improving Patient Outcomes Following Pediatric Liver Transplant: Current Perspectives</p>

Abstract: Over the last 50 years, considerable advances have been made in pediatric liver transplantation. The long-term 10-year patient and graft survival following pediatric liver transplant have improved considerably to greater than 90% and 75%, respectively. With longer living grafts, patients are now struggling with different issues, such as the consequences and morbidity of immunosuppression and/or chronic hospitalization. This review will discuss some of the current outcomes and obstacles in pediatric liver trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…The patient and graft survival rates in this study are comparable, in part superior, to those previously reported in the literature [9,23,24]. The largest series published so far on pediatric liver transplantation demonstrated 1-year survival rates of 84.4% in the last cohort (2013-2019) [25].…”
Section: Discussionsupporting
confidence: 81%
“…The patient and graft survival rates in this study are comparable, in part superior, to those previously reported in the literature [9,23,24]. The largest series published so far on pediatric liver transplantation demonstrated 1-year survival rates of 84.4% in the last cohort (2013-2019) [25].…”
Section: Discussionsupporting
confidence: 81%
“…Whilst long-term outcomes may vary across different geographical locations, the general themes remain the same [13,14] These long-term issues include graft disease, side effects of immunosuppression, poor growth and metabolic syndrome, and the psychosocial impact of transplantation as they transition to adult care. Few reports have addressed 20-year pLT survivors, and even fewer have focused on the biopsychosocial outcomes of these survivors [13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…KTx is the optimal treatment for end-stage kidney failure due to several causes both in adults and in younger patients [5,6]. It is important to understand that as the survival rate increases, at the same time, it increases the risk of developing further diseases in these patients, often due to the medications used [7]. In particular, LTx can lead to kidney injury, diabetes, infectious diseases, deficits or delays in childhood development.…”
Section: Introductionmentioning
confidence: 99%